Exploring EFL Students' Perceptions: The Role of AI Chatbots in Enhancing English Writing Skills - Masita; Hanif Maulaniam Sholah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This explanatory sequential mixed-methods study investigates how secondary EFL learners perceive and ethically integrate generative AI chatbots into academic writing. Grounded in an expanded Technology Acceptance Model (TAM), it addresses qualitative experiences and spiritual ethical boundaries within Islamic educational environments. Quantitative survey data were gathered from 20 MAN 1 Malang students, followed by semi-structured interviews with five selected participants, analyzed using Braun and Clarke’s thematic framework. Findings reveal high AI adoption; 100% of survey respondents agreed on task efficiency and grammar correction. Qualitatively, students utilize AI as an interactive scaffold to overcome writer’s block, structure outlines, and reduce writing anxiety. However, learners maintain critical agency regarding AI